Eber Teter journal - Teter, Eber, 1806-1878.
Typescript of a journal in which Teter describes his travels from Virginia through Ohio and Indiana to Illinois and back including comments on timber and agriculture and a list of his expenses.
Positive photocopy of typewritten transcript.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Agriculture -- Illinois; Agriculture -- Indiana; Agriculture -- Ohio; Agriculture -- Virginia; Timber -- Illinois; Timber -- Indiana; Timber -- Ohio; Timber -- Virginia; Illinois -- Description and travel; Indiana -- Description and travel; Ohio -- Description and travel; Virginia -- Description and travel; Clergy